Correlation of peripheral olfactomedin 1 with Alzheimer’s disease and cognitive functions - Chunxiao Wei; Guimei Zhang; Xiaoshu Fu; Meng Zhao; Weijie Zhai; Yanxin Shen; Li Sun (Translational Psychiatry)
Abstract Olfactomedin 1 (OLFM1) is thought to be involved in neuronal development, synaptic structure and function. However, the expression level of peripheral OLFM1 in Alzheimer’s disease (AD) and its role in AD are unclear. The present study was conducted to assess the relationship of serum OLFM1 with AD and cognitive function. This study comprised 120 patients with AD and 118 healthy controls (HC). Serum OLFM1 levels, cognitive functions, and brain region volumes were evaluated in all participants. The results demonstrated a significant reduction in serum OLFM1 levels in AD patients (749.8 ± 42.3 pg/mL) compared to HC (804.4 ± 45.7 pg/mL). Among participants carrying the APOE ε4 allele, a significant positive correlation was observed between OLFM1 levels and cognitive assessments, including Mini-Mental State Examination (MMSE), Montreal Cognitive Assessment (MoCA), and Memory and Executive Screening (MES). Furthermore, reduced OLFM1 levels were significantly associated with hippocampus (β = 0.005, 95% CI = 0.001–0.011, p = 0.042) and angular gyrus (β = 0.012, 95% CI = 0.001–0.022, p = 0.025) atrophy. The integration of serum OLFM1 with basic clinical characteristics exhibited robust discriminatory power in differentiating AD patients from HC, evidenced by an area under the curve of 0.881 (95% CI = 0.834–0.926). In summary, serum OLFM1 is a potential peripheral biomarker for AD, that correlates with cognitive function and specific brain volumes. In addition, APOE ε4 may modulate the influence of OLFM1 on cognitive function.